(untitled) (Dhaka University Journal of Biological Sciences, 2024)
Childhood maltreatment is the potential background under the umbrella of adverse childhood experience (ACE). The history of childhood trauma as well as child abuse can be affected lifelong through their adulthood stages. In addition, suicide is the most global issue among young generation. The present focused study determined to get the essence of the direction into the relationship between childhood maltreatment and suicidal ideation among adults in Bangladesh context. The cross sectional survey design was adopted for data collection purpose among 160 adults having age ranges between 18 to 40 years. Correlation analysis findings recommended that there is a strong association between childhood maltreatment and suicidal ideation (Spearman’s rank order correlation coefficient, r = 0.80, p < 0.01) and (Kendall’s tau-b rank order correlation coefficient, r = 0.62, p< 0.01). Furthermore, controlling with another aspect of chronological age, socio-economic status, profession and mental health service also indicating a moderate strong relationship between childhood maltreatment and suicidal ideation (Partial correlation coefficient, r (160) = 0.62, p < 0.01), (Partial correlation coefficient, r (160) = 0.63, p < 0.01), (Partial correlation coefficient, r (160) = 0.60, p < 0.01) and (Partial correlation coefficient, r (160) = 0.68, p < 0.01). The present research is the resource for mental health practitioner, academia, researcher, professional child psychologist, scholar, social worker etc who are willing to influence and contribute in mental health areas. Dhaka Univ. J. Biol. Sci. 33(1): 47-55, 2024 (January)